2000
DOI: 10.1021/bi002174z
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Nucleoside Triphosphates during RNA-Catalyzed Primer Extension

Abstract: In support of the idea that certain RNA molecules might be able to catalyze RNA replication, a ribozyme was previously generated that synthesizes short segments of RNA in a reaction modeled after that of proteinaceous RNA polymerases. Here, we describe substrate recognition by this polymerase ribozyme. Altering base or sugar moieties of the nucleoside triphosphate only moderately affects its utilization, provided that the alterations do not disrupt Watson-Crick pairing to the template. Correctly paired nucleot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 37 publications
3
18
0
Order By: Relevance
“…Furthermore, these protein enzymes and the ligase show a similar stereospecific response to sulfur substitution at the reactive phosphate, which is consistent with the idea that one of these essential metal ions may be bound in the same position relative to substrate in both catalysts (Eckstein 1985;Glasner et al 2000). This finding leaves open the possibility that the ligase uses the same mechanism as that proposed for general protein-catalyzed phosphoryl transfer, and prompts questions of whether the ribozyme might also share structural features with analogous protein enzymes.…”
Section: Introductionsupporting
confidence: 84%
“…Furthermore, these protein enzymes and the ligase show a similar stereospecific response to sulfur substitution at the reactive phosphate, which is consistent with the idea that one of these essential metal ions may be bound in the same position relative to substrate in both catalysts (Eckstein 1985;Glasner et al 2000). This finding leaves open the possibility that the ligase uses the same mechanism as that proposed for general protein-catalyzed phosphoryl transfer, and prompts questions of whether the ribozyme might also share structural features with analogous protein enzymes.…”
Section: Introductionsupporting
confidence: 84%
“…This is based on the observation that reaction time courses for the Ca 2+ -preincubation experiments fit a singleexponential curve, even at high pH, as expected for a homogeneous population of molecules that are correctly folded at the moment of Mg 2+ addition. The chemical step (R f ‚S f P + PP i ) is represented as irreversible because previous work has shown that the reverse reaction (pyrophosphorolysis with formation of a triphosphate) is 10 7 -times slower than the forward reaction (21).…”
Section: Role Of Metal Ions In Structure Andmentioning
confidence: 99%
“…Kinetic analysis of target-bound clone 21 half-ribozyme activity with the variant substrate RNA pairs indicates that substrate RNA complex recognition and utilization is not identical to that reported for the constitutively active Class I ligase Bergman et al 2000;Glasner et al 2000Glasner et al , 2002. Most strikingly, mutation of A3 only slightly decreased (A3G and A3C) or increased (A3U) activity, although this position is highly conserved in the Class I ligase.…”
Section: Remodeling Of the Class I Ligase Motifmentioning
confidence: 78%
“…Although in principle this approach is general to large ribozymes that use extensive Watson-Crick base pairs, we developed it using the extensively characterized Class I ligase motif of Bartel and colleagues Bergman et al 2000;Glasner et al 2000Glasner et al , 2002.…”
Section: Half-ribozymesmentioning
confidence: 99%